the impact of language use bullying on Indonesian students' language development - rezqan noor Farid; andriany hadisyah (Universitas Lambung Mangkurat, 2020)
Bullying is an issue that is difficult to be eliminated even in high education level. Bullying in high education may interfere the learning processes. Some of the students think that bullying is common. However, some others think that it is a bad situation for them. The study was conducted in University of Muhammadiyah Banjarmasin. The subject of this study is students of Intensive English Class. Case study is implemented to collect in-depth information about bullying factors in Intensive English Class. From indepth interviews that were conducted, the researcher found out that bullying factors included aspects of humiliation and mocking, intimidating, Ignoring, and Criticizing one’s appearance or background. The impacts found are considered safe and not severe since bullying in language use only caused shyness and not affecting the development of English learning.